2016
DOI: 10.1002/2015jb012219
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity of NaCl‐H2O fluid in the crust

Abstract: Ionic electrical conductivity of NaCl‐H2O fluid as a function of pressure (0.2–2.0 GPa), temperature (673–2000 K), and NaCl concentration (0.6–9.6 wt %) was investigated using molecular dynamics (MD) simulations. Conductivity versus NaCl concentration has a nonlinear relationship due to the presence of electrically neutral ion pairs in concentrated solutions. The calculated conductivity at 0.6 wt % NaCl is consistent with the available experimental data, and the calculated conductivity at higher temperatures s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 69 publications
2
46
0
Order By: Relevance
“…Sakuma and Ichiki () use molecular dynamics calculations to argue that salinities of 0.5 wt % NaCl are sufficient to explain the conductivity anomalies with fluid fractions of 1%, further pointing out that the critical dihedral angle, and hence connectivity, is a function of fluid fraction. Sakuma and Ichiki () somewhat underestimate the conductivity of the anomaly in the models of McGary et al () and so likely underestimate either the fluid salinity or volume fraction but not by a large amount: for example, assuming a salinity of 0.5 wt % would require fluid fractions of 3–4 vol %, which is close to the lower bound we calculate from our estimated fluid conductivities. Higher salinities would decrease the amount of fluid required to generate the observed conductivity anomalies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sakuma and Ichiki () use molecular dynamics calculations to argue that salinities of 0.5 wt % NaCl are sufficient to explain the conductivity anomalies with fluid fractions of 1%, further pointing out that the critical dihedral angle, and hence connectivity, is a function of fluid fraction. Sakuma and Ichiki () somewhat underestimate the conductivity of the anomaly in the models of McGary et al () and so likely underestimate either the fluid salinity or volume fraction but not by a large amount: for example, assuming a salinity of 0.5 wt % would require fluid fractions of 3–4 vol %, which is close to the lower bound we calculate from our estimated fluid conductivities. Higher salinities would decrease the amount of fluid required to generate the observed conductivity anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…As a conservative estimate, if we assume that all of the conduction at the peak is attributed to free fluids in a parallel circuit, then the fluid conductivities range from~2.5 to 6 S/m over the range of pressure considered. Sakuma and Ichiki (2016) use molecular dynamics calculations to argue that salinities of 0.5 wt % NaCl are sufficient to explain the conductivity anomalies with fluid fractions of 1%, further pointing out that the critical dihedral angle, and hence connectivity, is a function of fluid fraction. Sakuma and Ichiki (2016) somewhat underestimate the conductivity of the anomaly in the models of McGary et al (2014) and so likely underestimate either the fluid salinity or volume fraction but not by a large amount: for example, assuming a salinity of 0.5 wt % would require fluid fractions of 3-4 vol %, which is close to the lower bound we calculate from our estimated fluid conductivities.…”
Section: Application To Electromagnetic Studies Of Subduction Zonesmentioning
confidence: 99%
“…According to the laboratory conductivity data for important hydrous minerals in the subduction zone ( Figure 6), the dehydration of some hydrous minerals such as amphibole [Wang et al, 2012] and talc [Wang and Karato, 2013] cannot be the cause of the anomalous high conductivity in spite of the presence of aqueous fluids released during dehydration reaction. On the other hand, it has been suggested that the high conductive accessory minerals such as oxides (magnetite), phlogopite, and sulfides (or saline fluids) could account for the high conductivity anomalies in subduction zones by the conductivity model of two phase medium consisting of a resistive matrix and those conductive materials [Reynard et al, 2011;Li et al, 2016;Manthilake et al, 2016;Sakuma and Ichiki, 2016]. These results are somewhat efficient for the interpretation of some regional highly conductive anomalies, but not consistent with the widespread interpretation of highly conductive zones in terms of partial melting or the accumulation of free fluids [Ichiki et al, 2000;Soyer and Unsworth, 2006;Worzewski et al, 2011;Evans et al, 2014;McGary et al, 2014;Pommier, 2014].…”
Section: Implications For Highly Conductivity Anomalies In Subductionmentioning
confidence: 99%
“…2b). The correction to saline fluid conductivities from molecular dynamics data (Sakuma and Ichiki 2016) results in a 50 % increase of maximum salinities with respect to former estimates (Hyndman and Shearer 1989;Reynard, et al 2011), without affecting substantially their general conclusions because salinities change over more than one order of magnitude.…”
Section: Magnetotelluricsmentioning
confidence: 99%
“…The simple expression used by these authors has been shown to overestimate slightly conductivity at high salinities, and a more precise salinity-pressure-temperature-conductivity relationship was established from molecular dynamics (Sakuma and Ichiki 2016). Saline fluid conductivity is not very sensitive to temperature and pressure in the range of the forearc mantle (0.5-2 GPa, 573-973 K), and a simple second-order polynomial expression was fitted to experimental (Quist et al 1968) and molecular dynamics data (Sakuma and Ichiki 2016) with a 30 % precision similar to discrepancies between datasets…”
Section: Magnetotelluricsmentioning
confidence: 99%